Disseram que essa casa ia cair, mas ela é madeira que não dá cupim: cotidiano e resistência no ylê asé oyá tòdé (Manaus-AM) - Rodrigues, João Victor Marques (Brasil, 2025)
This work explores the trajectory of Mãe Ligia, a Yalorixá living in the northern zone of Manaus, focusing on the dynamics of occupation, territory, marginality, and resistance that shape her life and religious practice. The primary objective of the research is to understand how her role in the terreiro, a sacred space under construction in the Alfredo Nascimento neighborhood, transcends the boundaries of religiosity to become a political and social act. Through an ethnographic approach that includes semi-structured interviews, participant observation, and the analysis of daily practices, the study investigates how the terreiro is consolidated as a territory of refuge, transformation, and resistance against religious racism, a manifestation of structural racism. The research also examines Mãe Ligia’s strategies of resistance in the face of social exclusion and symbolic violence, utilizing the concepts of margin (Das, 2020), occupation (Flores, 2021), and daily life (Das, 2020). The terreiro emerges as an active agent in creating new possibilities of existence, where spiritual and cultural practices reframe historical experiences of oppression. The findings reveal that Mãe Ligia's actions represent not only a response to the adversities of a peripheral context but also a symbol of resilience and the reconstruction of Afro-Brazilian identities in Manaus.